Late paleozoic brachiopod zonation in west and east-central Argentina and its correlation with other south american basins - Cisterna, Gabriela Adriana (2021)
Brachiopods, one of the most abundant and diversified groups in the late Paleozoic benthic marine communities, are not particularly time-sensitive fossils but have been considered good tools for characterizing, correlating and assigning a relative age to the sedimentary successions. Although the Argentinian brachiopod faunas are among the better known for the late Paleozoic of South America, the absence of more precise biostratigraphic markers, the scarce radiometric data available and the strong faunal provincialism, prevent developing a high-resolution scheme. However, the marine stratigraphic record of the Mississippian–Pennsylvanian in central-western Argentina, considered to be one of the most complete in the region, allows the confection of a brachiopod zonation that provides the basis for correlations with other South American basins. Five brachiopod zones are proposed, namely Azurduya chavelensis (Tournaisian–Visean) restricted to the Río Blanco Basin and also identified in northern Chile; Levipustula levis (late Serpukhovian–early Bashkirian), typically associated to the postglacial transgression of the second glacial episode identified in the region, and also recorded from the Bolivian Tarija Basin; Marginovatia peregrina-Maemia tenuiscostata (late Bashkirian–early Moscovian), a zone of local value defined in the Barreal Hill of the Calingasta-Uspallata basin; Tivertonia jachalensis-Streptorhynchus inaequiornatus (Moscovian), the most widely distributed and diversified in the Precordillera, developed in relatively warm temperate conditions; and the youngest Costatumlulus amosi (?Sakmarian–?Artinskian), a low-diversity brachiopod assemblage only recorded in the southernmost part the Calingasta-Uspallata Basin, whose biostratigraphic relationships with the TivertoniaStreptorhynchus Fauna still needs revision. It is also important to note that brachiopods of the Levipustula levis zone have a relatively coeval postglacial fauna (Aseptella-Tuberculatella/Rhipidomella-Micraphelia). The significant compositional differences identified between both faunas have been explained by a group of abiotic factors directly related to glacial retreat dynamics and the coastal configuration. Age of the brachiopod zones mentioned above is mainly based on the palynological-palaeofloristic information but radiometric data have been also provided for the Levipustula levis zone (319.57±0.09 Ma U-Pb ages dated from the Guandacol Formation) and the Tivertonia jachalensis-Streptorhynchus inaequiornatus zone (312.82±0.11 Ma U-Pb ages from the transgressive marine deposits of the Tupe Formation). In eastcentral Argentina, in the Sauce Grande Basin, brachiopod assemblages integrate the Tomiopsis harringtoni zone herein proposed, restricted to pre-Sakmarian because of the SHRIMP age of 280.8±1.9 Ma from tuff-rich levels in the Tunas Formation. This fauna appears typically associated with the postglacial Eurydesma Fauna also identified in the glacial sequences of the Paraná Basin, Brazil, as the Eurydesma-Lyonia Fauna.